Comparison between the Apfel Score and the Koivuranta Score in Predicting the Occurrence of Postoperative Nausea and Vomiting during General Anesthesia - Palupi, Isnafianing; Suwondo, Bambang Suryono (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Abstract Background: PONV is one of the side effects that often occur after general anesthesia, occurs in the first 24 hours post surgery and occurs in as many as 30-70% of hospitalized patients. PONV greatly avoided by most patients and anesthesiologists. Recent risk score for prediction of PONV has been used as a way to classify patients according to risk prediction and provide prophylaxis in accordance with this classification. For everyday clinical purposes, a simple risk score in easy to do and shows the correlation between the predicted incidence of PONV in patients hospitalized. In the clinical practice known various risk score for prediction of PONV as Apfel scores, Koivuranta scores, Sinclair scores, Palazzo scores, Gan scores, and Scholz scores varying accuracy. Methods: The research design was a cohort study with the total of 80 patients recruited. Ordinal and nominal data was analyzed using chi-square test. P value < 0,05 was declared significant with 95% confidence level. Measurements taken are incidence of PONV between Apfel scores to Koivuranta scores with PONV scores. Results: Incidence of PONV in patients who carried the scoring with Apfel scores higher (80%) than Koivuranta scores, and statistically highly significant differences (p < 0,01). The results said that Apfel scores are more accurate than the Koivuranta scores, indicated by results of PONV scores positive (>1) on the Apfel scores 32 people (80%) and on the Koivuranta scores 12 people (30%), whereas PONV scores negative (≤ 1) on the Apfel scores 8 people (20%) and on the Koivuranta scores 28 people (70%). Conclusions: Apfel scores are more accurate than the Koivuranta scores in predicting the occurrence of PONV in patients with general anesthesia.